UM breaks into top 30 in QS Asia rankings - Anand, Ram (The Edge Communications, 2015)
KUALA LUMPUR: Universiti Malaya (UM) broke into QS Quacquareli Symonds Asia's top 30 rankings as Malaysian universities across the board improved their rankings in the latest QS evaluation for 2015 released yesterday.